The association between lipid accumulation products and bone mineral density in U.S. Adults, a nationally representative cross-sectional study - Aiyong Cui; Yan Zhuang; Xing Wei; Shuang Han (Scientific Reports)
Abstract LAP (lipid accumulation products) is a new indicator that estimates lipid overaccumulation and central obesity in our bodies. Nevertheless, the relationship of LAP with bone mineral density (BMD) has not been well established. This study aims to assess the association of LAP with BMD in U.S. adults. Multivariate linear regression was employed to detect the relationship of LAP with lumbar BMD in adult Americans. Subgroup and interaction tests were employed to detect the robustness of our findings. Restricted cubic spline (RCS) and threshold effect analysis were used to assess the nonlinear correlation of LAP with lumbar BMD. A total of 3883 participants consisted of 2117 (54.52%) men and 1766 (45.48%) women. The mean age of participants was 39.33 ± 11.53 years. After adjusting all covariates, we found a negative association of ln-LAP with lumbar BMD (β= -0.011, 95% CI: -0.019, -0.004). Threshold effect analysis identified the inflection points of 2.846. The results showed no correlation to the left of the saturation point but a significant negative correlation to the right. Interaction analyses indicated that all subgroups have no effect on this association (P > 0.05). Our study reported a nonlinear negative association of LAP with lumbar BMD. A large LAP may be associated with reduced BMD in American adults. These findings support the clinical utility of LAP as a predictor of osteoporosis and provide valuable insights into developing early intervention strategies for osteoporosis populations.